Hubungan Antara Work Life Balance dan Stres Kerja Pada Karyawan - Maria Angelica Urba; Christiana Hari Soetjiningsih (Bulletin of Counseling and Psychotherapy, 2022)
Human resource is one of the resources that has an important role in achieving organizational goals. If an organization cannot balance time for work and family time, the individual will feel a conflict that can make an individual experience work stress. The study aims to determine the relationship between work-life balance and work stress on BULOG employees. This research is a quantitative correlational with a sample of 38 employees selected by using accidental sampling technique. The dimensions on the scale correspond to the dimensions desired by William & Cooper (1997), namely aspects of the work itself, role management, interpersonal relationships, organizational style, career development, and work-family conflict. Whereas the work life balance measurement tool in this study was adapted from the scale developed by Yusuf (2018), namely the work life balance inventory with a total of 13 item items and a cronbach's alpha of 0.806. The results obtained prove that there is a significant negative relationship between work life balance and work stress with a correlation coefficient of -0.606 with a significant value of 0.000 (p < 0.05). The findings show that the level of work-life balance and stress work of BULOG staff is in the current category.